The peach (Prunus persica) defensin PpDFN1 displays antifungal activity through specific interactions with the membrane lipids. (12th June 2012) - Nanni, V.; Zanetti, M.; Bellucci, M.; Moser, C.; Bertolini, P.; Guella, G.; Dalla Serra, M.; Baraldi, E.
<x xml:space="preserve">Abstract</x> Ppdfn1 is a defensin gene previously identified in peach (Prunus persica). The biological role of Ppdfn1 was investigated by analysing its expression profile in leaves, flowers and fruits, either inoculated with the Monilinia laxa fungal pathogen or mock‐inoculated. Ppdfn1 expression was highest in flowers and, in fruits, did not vary upon M. laxa inoculation. To characterize the PpDFN1 antifungal activity, the recombinant mature peptide was expressed in Escherichia coli and purified; recombinant PpDFN1 displays antifungal activity against Botrytis cinerea, M. laxa and Penicillium expansum, with IC50 values of 15·1, 9·9 and 1·1 μg mL−1, respectively. Treatment of fungal hyphae with FITC‐labelled PpDFN1 indicated that the peptide is not internalized by fungal hyphae, but localizes on their external cell surface. At this site, PpDFN1 is capable of membrane destabilization and permeabilization, as demonstrated by SYTOX Green fluorescence uptake by the treated mycelia. Using artificial lipid monolayers, it was shown that PpDFN1 interacts with sphingolipid‐containing membranes; however the strongest interaction occurs with monolayers composed of lipids extracted from sensitive fungi, such as P. expansum. These data suggest that the lipid composition of fungal membranes is of key relevance for defensin specificity.